From the history of St. Volodymyr University: Nazarii Antonovych Favorov - Нападиста, Валентина Григорівна (Київський національний університет імені Тараса Шевченка, 2019)
The article reconstructs the life and analyzes the main thematic components of the creative heritage of Nazariy Antonovich Favorov (1820-1897), Doctor of Theology, a professor who for almost four decades (1859-1897) taught moral theology at the St. Vladimir University and was the rector of the university church. Ideological and political prejudices have led to the long neglect of a highly respected, recognized person both by university tutors corporation and a wide circle of the public. N. A. Favorov is the author of many works on moral theology, in particular, "Essays on the Moral Orthodox-Christian Doctrine", which had seven editions, were highly appreciated by colleagues and for a long time were considered an official textbook on moral theology in Russia. The moralist-theologian concentrates his attention on the problems of the origin of morality, correlation of the morality doctrine with religious and philosophical foundations, the characteristic features of the moral activity subject, freedom of will and substantiation of its significance for the moral existence of man, moral choice, moral qualities and their place and role in the human essence. It was established that the main topics of his creative ideas were predominantly determined by the problems, established in moral theology, but N.A. Favorov did not overlook the issues relevant for academic philosophizing in Ukraine and the Western European ethical discourse of the second half of the nineteenth century. The semantic accents in the substantiation of N.A. Favorov's creative searches were based on the main provisions of the Orthodox religious doctrine. The work of N.A. Favorov, though not entirely original, has a thorough and holistic presentation of the main problems of the moral existence of man, widely spread in the educational space of Ukraine in the second half of the nineteenth century, making his creative legacy important and meaningful in the national historical and cultural context.

У статті здійснено реконструкцію життєвого шляху та проаналізовано основні тематичні складові творчого спадку Назарія Антоновича Фаворова (1820‒1897), доктора богослов’я, професора, який упродовж майже чотирьох десятиліть (1859‒1897) викладав моральне богослов’я в Університеті Св. Володимира та був настоятелем університетської церкви. Основна тематика моралістабогослова зосереджена навколо проблем походження моралі, кореляції вчення про мораль з релігійними та філософськими засновками, характерних ознак суб’єкта моральної діяльності, свободи волі та обґрунтування її значимості для морального буття людини, морального вибору, моральних якостей та їхнього місця і ролі у людській сутності. Смислові акценти при обґрунтуванні означених тематичних складових творчих студій Н. А. Фаворова базувалися на основних положеннях православної релігійної доктрини. Напрацювання Н. А. Фаворова хоч і не відзначаються цілковитою оригінальністю, та мають ґрунтовний, розлогий, цілісний виклад основних проблем морального буття людини, широко трансльований в освітньому просторі України другої половини ХІХ ст., що робить його творчий спадок вагомим та значущим в національному історико-культурному контексті.
З історії Університету Св. Володимира: Назарій Антонович Фаворов
Keywords: Університет Св. Володимира; Н. А. Фаворов; моральне богослов’я; моральна діяльність; свобода волі; моральний вибір; моральні якості; St. Volodymyr University; N. A. Favorov; moral theology; moral activity; freedom of choice; moral choice; moral qualities